CO-WORKING SPACE AS A CREATIVE-COLLABORATIVE SPACE OF COMMUNITY CENTRE IN PURWOKERTO - Leny Indah; Ofita Purwani; Leny Pramesti (ARSITEKTURA, 2018)
This paper concerns about Designing Community Centre in Purwokerto as Creative-Collaborative space by using co-working space. Co-working space is one way to induce creative ideas, because it makes it possible for people to share and learn together with other people from different background. This space also anables people to connect and collaborate to create ideas.As Purwokerto is one of the cities in Indonesia whose concern about developing its creative communities, this city has a potential to be the locus for the Community Centre. This article will then focus on the designing of the Community Centre by using co-working space for inducing creative and collaborative activities in Purwokerto. Some key aspects of co-working space to be applied in the design are the services, spatial layout and ambience of space.